“More than just a student”: How co-creation of the curriculum fosters third spaces in ways of working, identity, and impact - Lubicz-Nawrocka, Tanya Michelle (International Journal for Students as Partners, 2019)
The Third Space (Bhabha, 2004) represents non-traditional roles, processes, relationships, and spaces in which individuals work and have impact. This article presents qualitative research into 13 different curriculum co-creation initiatives at five Scottish universities and analyses the forms of Third Space that emerge.The findings highlight that curriculum co-creation can foster Third Spaces that include: new ways of working in learning and teaching, student development in a space between traditional student and teacher roles and identities, and impact in civic engagement within and beyond the university. The respect and reciprocity that characterise curriculum co-creation can greatly benefit students’ personal and professional development as individuals. In addition, I suggest that the Third Space of civic engagement can advance the Third Mission of universities (beyond impact in the first two missions of teaching and research) when students and teachers work in partnership to have a positive effect on the wider society.